UPAYA HUKUM TERHADAP DISTRIBUTOR BARANG KW - Theodor Manurung, Rachel Wahyunita; i, Urbanisasi (Peneliti.net, 2023)
The sales phenomenon of KW goods in Indonesia is increasing. This causes losses for consumers, brand owners and also the government. The purpose of this research is to find out legal remedies against the distribution of KW goods in Indonesia. The method used in this study is to use a descriptive analysis method with data collection techniques derived from secondary data. The results of the study show that legal protection efforts for the distribution of KW goods are regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications which discusses protection based on the first to file principle system and the first to file principle system. Articles included in legal protection efforts are articles 25, 26, and 27 of Law Number 20 of 2016.